STUDI PENGEMBANGAN MESIN STANDAR GAYA-TORSI HYBRID KAPASITAS RENDAH UNTUK KELAS INDUSTRI - Nurcahyono, Dinar; Nirbito, Wahyu; Hafid, Hafid (Pusat Penelitian dan Pengabdian Masyarakat, 2024)
The role of standard measurements for low-capacity forces and torques is increasingly more significant, along with the development of automation technology, micromachines, biomechanical systems, and so on, which are relatively small in size. The force and torque standard machine needs to be developed to meet these needs. In this research, a study was conducted to evaluate the possibility of making a low capacities hybrid torque-force standard machine, that is a deadweight force standard machine whose function is optimized so that it can also be used as a torque standard. This preliminary development is designed for a 2.5 N – 50 N force capacity and torque of 0.25 N·m – 20 N·m. The development of a design with a hybrid function as a torque standard is built using a detachable arm along with a wire sling and pulley bearing. The results of preliminary analysis and simulation calculations show that developing a standard low-capacity hybrid torque-force engine is possible. That is meeting the machine uncertainty requirement target of 0.1% for force quantities and 0.3% target for torque quantities. The target uncertainty value that can be achieved also depend on the manufacturing process.